Implication of taxonomic abundance of gut microbiota in prediabetes: a systematic review - Liberty, Iche Andriyani; Hanifah, Laily; Rachmat, Hanna Farida; Putri, Aidi Alifia; Pratiwi, Dessy; Pramono, Andri Pramesyanti; Idris, Fachmi; Tjekyan, Suryadi (Frontiers in Nutrition, 2025)
BackgroundPrediabetes is defined by blood glucose levels that are higher than normal but below the diagnostic threshold for diabetes. Environmental factors associated with diabetes may contribute to its development through alterations in the gut microbiota. Recent studies suggest that changes in the composition and function of the gut microbiota play a role in the pathogenesis of diabetes mellitus and other metabolic disorders.ObjectiveThis study aims to systematically examine taxonomic abundance and its implications in the gut microbiota of individuals with prediabetes, identify key dysbiotic patterns, and explore their potential role in inflammation, insulin resistance, and progression to type 2 diabetes.MethodsWe conducted a systematic literature review following PRISMA guidelines. The review included sources from PubMed, ClinicalKey, ScienceDirect, Springer, and Scopus. We retrieved original research articles published in English that focused on prediabetes and gut microbiota from 2015 to the date of our search. Out of 827 full-text articles screened, 6 were selected based on defined inclusion and exclusion criteria.ResultsDysbiosis of the gut microbiota in prediabetes is characterized by a reduction in butyrate-producing bacteria such as Faecalibacterium prausnitzii and Roseburia, along with an increase in potentially harmful taxa such as Escherichia/Shigella and Prevotella species. This imbalance is associated with systemic inflammation and insulin resistance, evidenced by elevated levels of C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and lipopolysaccharide-binding protein (LBP). Increased intestinal permeability facilitates the translocation of bacterial components such as lipopolysaccharides (LPS), further linking gut microbiota changes to the development of insulin resistance and type 2 diabetes.ConclusionThis review highlights the need for further research to explore the potential therapeutic role of gut microbiota in prediabetes.Systematic Review RegistrationProspero; Identifier CRD42025637369.